Composites and advanced materials testing relative to UAS at the National Institute for Aviation Research - Opliger, Matt (Kansas State University, 2014)
The Composites and Advanced Materials Laboratory at Wichita State University’s National Institute for Aviation Research has extensive experience and capabilities relative to UAS testing. Most of these tests are protected with tightly sealed nondisclosure agreements, however, the lab’s experience includes qualification of materials for numerous UAS programs and full-scale structural testing for the Boeing UCAS. NIAR’s Composites and Advanced Materials Lab has an international reach and reputation in material testing and qualification for composites and metals. Capabilities include lay-up, machining and bonding operations; environmental effects including heat, moisture, contamination and lightning strike; thermoset, thermoplastic and rapid prototyping; and static and fatigue testing for articles from small coupon samples to full-scale aircraft. Yearly the lab sends 45,000 coupon samples through machining and quality control, sets 30,000 strain gauges and tests 34,000 coupon samples. The lab boasts additional capabilities since the expansion of its Aircraft Structural Test and Evaluation Center to the former Britt Brown Arena at the Kansas Coliseum, including increased space and staff to accommodate concurrent testing and the addition of a 500-kip axial torsion load frame. The 500-kip frame is can apply up to 500,000 pounds of axial force along with with 60,000 ft-pounds of torque and has an active working region of approximately eight feet. The lab has instant access to qualified materials systems through the university’s FAA-funded National Center for Advanced Materials Performance and the Composites Materials Handbook, published by WSU. The goal of the presentation is to expand on these relationships and capabilities for the benefit of the Kansas UAS industry.
Keywords: Wichita State University; National Institute for Aviation Research; Composites and Advanced Materials Laboratory; Material testing